Case report: fatal pneumonia caused by new sequence type Legionella pneumophilia serogroup 1. Issue 43 (23rd October 2020) - Jiang, Luxi; Tao, Sixu; Mu, Deguang; Zhang, Naxin; Zhao, Li; Chen, Yu
Abstract: Introduction: Legionnaires' disease is caused by Legionella bacteria, and commonly manifests as pneumonia and has a high fatality rate. Patient concerns: This case study reports on the fatal incident of a patient, initially diagnosed with pneumonia, and subsequently diagnosed with Legionnaires' disease caused by a new sequence type (ST) of Legionella. Diagnosis: It is speculated that the patient acquired Legionnaires' disease from a contaminated water source. Legionnaires' disease was diagnosed using the Legionella urinary antigen assay and bacterial cultures of respiratory secretions; Legionella pneumophilia Type 1 was also identified through serological testing. Sequence-based typing of the cultured bacterium revealed it to be a previously unidentified species, and it was named ST2345 new-type. Interventions: In addition to the treatment of Legionnaires' disease, blood samples taken on the second day of admission showed a co-infection of Candida tropicalis, which was treated with anti-fungal treatment. The patient improved after a week, however, on the seventh day of administration lower respiratory secretions showed the growth of Klebsiella pneumonia, indicative of ventilator-associated pneumonia. Outcomes: Despite active treatment, the patient passed away due to multiple organ failure. As this was a fatal case, further research is needed to determine whether the critical condition of this case was related to the virulence of the novel Legionella strain. Conclusion: A key finding of this study is that treatment for suspected Legionnaires' disease must be administered rapidly, as infection with Legionella may give rise to secondary pathogenic infections.